Comparative analysis of diagnostic accuracy between transoral and submental contrast-enhanced ultrasound-guided biopsy for tonsillar tumors - Wei, Ting; Lu, Man; Li, Tingting; Hu, Ziyue; Wang, Lu; Li, Juan; Dai, Jiulong; Wu, Xiaobo; Tan, Bo; He, Fawei; Li, Yuan; Yang, Wei (Frontiers in Oncology, 2025)
ObjectiveTo assess and compare the diagnostic accuracy and safety of contrast-enhanced ultrasound (CEUS)-guided transoral and submental core needle biopsy (CNB) techniques in patients with suspected tonsillar masses, and to identify which approach offers superior diagnostic performance with fewer complications.MethodsBetween November 2019 and March 2024, 41 patients with suspected tonsillar masses were enrolled in this comparative study of two biopsy techniques. Each patient underwent either a transoral CNB or a submental CNB. Diagnostic metrics, including accuracy, sensitivity, negative predictive value (NPV), and positive predictive value (PPV) were calculated for each method. Pain levels before and after the procedures were recorded to evaluate patient discomfort, and any complications were documented to evaluate safety. Statistical analyses were conducted to determine whether differences in diagnostic performance, biopsy time, and complication rates between the two techniques were significant.ResultsA total of 41 patients were included in the analysis (transoral CNB, n = 22; submental CNB, n = 19). The transoral approach demonstrated higher diagnostic accuracy (95.45% vs. 89.47%), sensitivity (91.67% vs. 87.5%), and NPV (90.91% vs. 60.00%) compared with the submental approach; PPV was 100% for both methods. Pre- and post-biopsy pain scores were similar in both groups, with no significant differences observed. No significant complications occurred in the transoral group. In the submental group, two patients developed minor acute submandibular adenitis; however, this difference in complication rates (0% vs. 10.5%) was not statistically significant (P = 0.21).ConclusionThe transoral CEUS-guided CNB approach demonstrated higher diagnostic accuracy and lower post-procedural complication rates than the submental method in the evaluation of tonsillar tumors. These findings support the transoral route as the preferred technique for obtaining tonsillar biopsy specimens and may inform clinical practice changes aimed at improving patient outcomes through more accurate and timely diagnosis.